(untitled) (Research, Society and Development, 2022)
Critical patients admitted to Intensive Care Units (ICU) are at high risk for developing stress ulcers or gastrointestinal bleeding, so there are recommendations on the use of prophylactic drugs for this event, such as proton pump inhibitors in these patients. Therefore, this study aims to analyze the literature on the effects of proton pump inhibitors use in patients admitted to intensive care units. In this sense, articles were collected in the MEDLINE databases, through the search engine Public/Publisher MEDLINE (PubMed) and BVS - Virtual Health Library -. The descriptors of interest found through the Medical Subject Headings (MeSH) tool were “Proton Pump Inhibitors” AND “Intensive Care Unit”, which were selected based on previous publications on the object of study and combined in the strategy of elucidated search. 16 of the 553 articles found with the search were included in this review. Furthermore, there was an analysis of the level of evidence and the degree of recommendation of the articles according to the Oxford Center Evidence-Based Medicine system. It is concluded, according to the studies analyzed, that there is divergence in the literature regarding the definition of the effects of this drug class in ICU patients, in which outcomes such as bloodstream infection, pneumonia, mortality, and superiority in preventing bleeding provided by the use of proton pump inhibitors is not fully in agreement among the articles studied. Thus, further studies are needed to understand the effects of proton pump inhibitors in ICU patients.